Comparative Study of Environmental Challenges of Urmia Lake and Aral Lake in order to Protect and Rehabilitate Urmia Lake - Kimiasadat Doratotaj; Ali Zare; Mansour Pournouri (Environmental Energy and Economic Research, 2022)
One of the main issues of the present age is the environment and understanding its significant contribution to our lives. The environment has currently found a special place and importance. Wetlands are one of the most valuable ecosystems on earth, offering a wide range of biodiversity. The Ramsar Convention on Wetlands was signed in 1971 due to the special status and value of this ecosystem. One of the largest wetlands on the list of conventions is Lake Urmia, which Iran has committed to protect and use reasonably. However, natural and human factors, including the construction of the Shahid Kalantari Highway and dozens of dams and the agricultural sector, have led to numerous environmental challenges such as the reduction of the lake area, and the reduction of the lake water level, and the production of harmful dust storms. Accordingly, the present study examined the domestic and international laws concerning Lakes Urmia and Aral to present a suitable solution for the environmental challenges of Lake Urmia, along with its conservation and rehabilitation.